Lifelong Learning principles and higher education policies - Carlos Vargas (Universidad de Deusto, 2014)
The role of higher education in promoting economic growth and social cohesion has been recognised in multiple international documents, programmes and strategies. Likewise, a number of countries and higher education institutions worldwide have introduced policies that aim at fostering learners' employability, active citizenship, personal development, knowledge base, competences and capabilities. However, not all these policies have successfully addressed current global trends like the economic downturn, demographic change, the changing nature of the labour market, and pressing social needs. This paper posits that introducing lifelong learning principles to the formulation and implementation of higher education policies may provide more inclusive and comprehensive frameworks for meeting the needs and aspirations of the multiple stakeholders of higher education.